Reporting Recommendations for Tumor Marker Prognostic Studies (REMARK): explanation and elaboration. - Altman, D; McShane, L; Sauerbrei, W; Taube, SE (Public Library of Science, 2012)
The REMARK (Reporting Recommendations for Tumor Marker Prognostic Studies) guideline includes a checklist which aims to improve the reporting of these types of studies. Here, we expand on the REMARK checklist to enhance its use and effectiveness through better understanding of the intent of each item and why the information is important to report. Each checklist item of the REMARK guideline is explained in detail and accompanied by published examples of good reporting. The paper provides a comprehensive overview to educate on good reporting and provide a valuable reference of issues to consider when designing, conducting, and analyzing tumor marker studies and prognostic studies in medicine in general.